IMPROVING STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT BY USING MOVIE POSTERS - Ayu - Saleha; Sumarsih - - (Universitas Negeri Medan, 2014)
ABSTRACT This study concerns on Improving Students’ Achievement in Writing Descriptive Text by Using Movie Posters. The underlying objective of this study is to investigate whether teaching descriptive by using movie posters potentially improves students’ skill. The research was conducted by using Classroom Action Research (CAR). The subject of the research was class X of SMA SWASTA UTAMA MEDAN. The number of the students was 28. The procedure of the research was administrated into two cycles which each cycle consisted of three meetings. Each meeting included four steps namely: planning, action, observation and reflection. There were two kinds of data collected during the study, qualitative and quantitative data. The instrument for collecting the quantitative data was the writing of descriptive text. The qualitative data were gathered by using diary notes, observation sheet and questionnaire sheet. Based on the data analysis, the mean of students’ scores in Test I was 45.71; Test II was 62.32 and Test III was 81.96. The quantitative & qualitative data showed that the students were interested in using movie poster as a media in learning descriptive text. The conclusion is the using of movie poster as a media in teaching-learning process improves students’ achievement in writing descriptive text. Keywords: Descriptive Text, Movie Poster, Classroom Action Research